STATISTICAL ANALYSIS OF TRIBOLOGY FRICTION DATA IN A LONG REPEATED SLIDING SYSTEM - prof. Kanao Fukuda; ass. O.Qurbonov; ass. H.Axralov (International Journal of Innovations in Engineering Research and Technology, 2021)
Though understanding fundamental mechanisms of phenomena is of decisive importance for the contribution of tribology to society, those mechanisms have not yet been clarified sufficiently. As the requirements on the quality of tribological components continue to rise, the need for understanding the factors that govern their properties also rise. A tribological phenomenon, especially siding, is widely recognized as a time-dependent phenomenon and a running-in processand a severe-mild wear transition are typical examples(Lancaster, 1963). Some of the efforts made to understand adhesive wear phenomena were headed to atomic to nano-level approaches such as experimental analysis using SPM (scanning probe microscopy) (Sato et.al, 2016)and numerical simulations e.g. molecular dynamics simulations on interactions of atoms etc. (Shimizu, Zhou & Yamamoto, 2013). Novel analysis method was devised to studyrepeated sliding phenomena and the method enabled the visualmapping of dynamic information e.g. friction force and pin-displacement on a plane which employs two axes normal to each other ofsliding position and the number of repeated sliding (Fukuda,2004).